Characterization of Involuntary Contractions after Spinal Cord Injury Reveals Associations between Physiological and Self-Reported Measures of Spasticity - Mayo, Meagan; DeForest, Bradley A.; Castellanos, Mabelin; Thomas, Christine K. (Frontiers in Integrative Neuroscience, 2017)
Correlations between physiological, clinical and self-reported assessments of spasticity are often weak. Our aims were to quantify functional, self-reported, and physiological indices of spasticity in individuals with thoracic spinal cord injury (3 women, 9 men; 19-52 years), and to compare the strength and direction of associations between these measures. The functional measure we introduced involved recording involuntary electromyographic activity during a transfer from wheelchair to bed which is a daily task necessary for function. High soleus and tibialis anterior F-wave/M-wave area ratios were the only physiological measures that distinguished injured participants from the uninjured (6 women, 13 men, 19-67 years). Hyporeflexia (decreased soleus H/M ratio) was unexpectedly present in older participants after injury. During transfers, the duration and intensity of involuntary electromyographic activity varied across muscles and participants, but coactivity was common. Wide inter-participant variability was seen for self-reported spasm frequency, severity, pain, and interference with function, as well as tone (resistance to imposed joint movement). Our recordings of involuntary electromyographic activity during transfers provided evidence of significant associations between physiological and self-reported measures of spasticity. Reduced low frequency H-reflex depression in soleus and high F-wave/M-wave area ratios in tibialis anterior, physiological indicators of reduced inhibition and greater motoneuron excitability, respectively, were associated with long duration soleus and biceps femoris electromyographic activity during transfers. In turn, participants reported high spasm frequency when transfers involved short duration tibialis anterior EMG, decreased co-activation between soleus and tibialis anterior, as well as between rectus femoris versus biceps femoris. Thus, the duration of muscle activity and/or the time of agonist-antagonist muscle coactivity may be used by injured individuals to count spasms. Intense electromyographic activity and high tone related closely (possibly from joint stabilization), while intense electromyographic activity in one muscle of an agonist-antagonist pair (especially in tibialis anterior versus soleus, and rectus femoris versus biceps femoris) likely induced joint movement and was associated with severe spasms. These data support the idea that individuals with spinal cord injury describe their spasticity by both the duration and intensity of involuntary agonist-antagonist muscle coactivity during everyday tasks.